The Development of an Introduction to the Educational Field Model for the Bachelor of Transformative Education Program in Islamic Higher Education - Siti Halimah; Rusydi Ananda; Farida Jaya (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to find a valid and effective model for introducing the field of transformative education. The research method used is Research and Development. To obtain initial data related to the focus of this analysis, the researchers conducted interviews and documentation studies to: (1) 5 students randomly selected who had followed the PPL which were seen from the background of the study program, motivation, goals and expectations for joining the PLP-PSP. ; (2) 2 supervising lecturers and PLP-PSP civil servant teachers; (3) the head of the study program; (4) deputy dean I as deputy dean for academics; and (5) documentation study of PLP-PSP documents and literature related to PLP-PSP. Validation, evaluation, and revision are carried out to obtain clarity, material quality and attractiveness of the resulting product. The results of this study conclude that the model of teaching materials designed meets the correct procedures and is feasible to use.